Design and simulation of a fan-shaped banana cutting machine - Dian Panutan; Mustaza Ma'a; Agus Wijianto; Roni Novison (JTTM : Jurnal Terapan Teknik Mesin, 2025)
The fan-shaped banana cutting machine is an innovative solution for banana processing that focuses on mechanical efficiency without using complicated electronic sensors. The machine has four main mechanisms consisting of cutting, pushing, conveyor, and a rotating plate mechanism. The cutting mechanism uses four sharp blades to slice each banana into five fan-shaped pieces, with an average banana weight of 100 grams. The machine can cut up to 30 bananas per minute with a pulley speed of 30 RPM, making it fast and consistent. The pushing and conveyor mechanism work together to move the bananas into position for cutting and transport the slices smoothly. The rotating plate is designed to collect up to five sliced bananas in one cycle. This study explains the design and testing process using motion analysis software to make sure the machine works well. The simulation looked at the movement, power use, and efficiency of each mechanism of the machine. The results showed the total power needed is 4.4 Watts, with 2.4 Watts for cutting mechanism, 0.12 Watts for the pushing mechanism, 1.26 Watts for the conveyor mechanism, and 0.62 Watts for the rotating plate mechanism. A 0.25 HP motor with a speed reducer (1:47 ratio) was chosen to run the machine efficiently.The design focuses on mechanical systems, making it simple and reliable for small-scale production. This machine is a cost-effective and practical option for improving productivity in banana processing. The study provides a strong foundation for future mechanical innovations in food processing technology.